2019
DOI: 10.3390/agronomy9040183
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Carbon and Water Fluxes of Managed Grasslands: Comparing Flux Variability and Net Carbon Budgets between Grazed and Mowed Systems

Abstract: The CenW ecosystem model simulates carbon, water, and nitrogen cycles following ecophysiological processes and management practices on a daily basis. We tested and evaluated the model using five years eddy covariance measurements from two adjacent but differently managed grasslands in France. The data were used to independently parameterize CenW for the two grassland sites. Very good agreements, i.e., high model efficiencies and correlations, between observed and modeled fluxes were achieved. We showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 97 publications
(155 reference statements)
1
27
1
Order By: Relevance
“…Puche et al. (2019) performed a similar study in France. Using multi‐model ensembles in scenario studies at eight sites worldwide, Basso et al.…”
Section: Introductionmentioning
confidence: 96%
“…Puche et al. (2019) performed a similar study in France. Using multi‐model ensembles in scenario studies at eight sites worldwide, Basso et al.…”
Section: Introductionmentioning
confidence: 96%
“…Montado ecosystems are particularly complex and difficult to study because of the wide range of management and environmental conditions that they are exposed to [3]. The results of this study demonstrated the effect of trees and their importance in the dynamics of soil nutrients in agro-silvo-pastoral systems and highlighted the importance of optimizing the management of pasture and animal grazing as a potential measure for mitigating climate change in Mediterranean regions.…”
Section: Soil Spatial and Temporal Variabilitymentioning
confidence: 72%
“…This system is characterized by a high complexity resulting from the interactions between climate, soil, pasture, trees, and animals [2]. Montado and pasture production are very important farming systems since, in Portugal, this ecosystem represents 33% of total forest area [2] and in Europe, grasslands cover 22% of the land area [3]. Since the turn of the new millennium, greater recognition of the importance of grasslands in conserving soil, promoting biodiversity, stabilizing farming communities, and providing a wealth of natural ecosystem services has led to renewed interest in the dynamics of grasslands function [4].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, models need to be tested and verified against real-world observations to build confidence in their ability to accurately describe the patterns we are interested in, in particular, the effect of different management options in enhancing soil organic carbon storage without compromising pasture productivity. The contribution from Puche et al [25] is a modeling work on mown and grazed paddocks in France, equipped with eddy-covariance (EC) measuring systems. The model used, CenW, confirms the difficulty of simulating grazing systems where EC devices may not completely detect C losses.…”
Section: Soil Fertility and Modelingmentioning
confidence: 99%